An Application of Reverse Transcriptase Polymerase Chain Reaction in A Relative Quantification of Gene Expression - Santoso, Adi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2004)
The ability to quantify steady state levels of individual mes enger-RNA (mRNA) transcripts has been the key issue for study on the control of gene expression. Although two available techniques, Northern blot and nuclease protection assays (NI)A) have been widely used tor detecting mRNA, these techniques have critical limitations. The most obvious limitation of these two techn iques is the required number of target mRNAs to be detected. Reverse transcription-polymerase chain reaction (RT-P R), which has been accepted as a highly sensitive and specific method, provides a means for detecting and quantifying gene expression using, theoretically only a single molecule of mRNA. The ensitivity and reliability ofRT-PCR i dependent upon both the RT and PCR steps. The PCR step ha been problematic because of the exponential nature of this reaction where small variation can lead Lo dramatic changes in final result. here fore, the use of RT-P R for quanti fication of gene expres ion requires pre-experimental planntng and de ign. In thiS experiment, the procedure fOT pre-experimental planning, linear range determination and subsequent relative quantification of gene expression are described in detail. study of ornithine decarboxyJase gene, a gene involved in the polyamine biosynthesis and temporally expressed, dunng embryogenesis of Musca domestica (housefly) was used as the model. The re ults show that during early embryogenesis (t-l to t-4) the expression lev I was very low. The increase In expression profile was observed started at t-5, peaked at t-9, and followed by substantial decrease from t-l 0 to t- 12. Â